Integrative analysis of pectin methylesterase (PME) and PME inhibitors in tomato (Solanum lycopersicum) Identification, tissue-specific expression, and biochemical characterization - Jeong, Ho Young (Plant physiology and biochemistry : PPB, 2018)
Copyright © 2018 Elsevier Masson SAS. All rights reserved.